Analysis of the thermal performance and comfort conditions of vernacular rammed earth architecture from southern Portugal - Fernandes, J. E. P. (2020)
Vernacular architecture has developed several passive strategies to respond to specific climate conditions. In the last few decades, vernacular architecture has been the subject of several qualitative and quantitative studies on the scope of sustainability. The results showed that they have the potential to reduce the energy demand from nonrenewable sources during the operation stage. This article analyzes the effectiveness of passive strategies in the thermal performance of a rammed earth building located in southern Portugal, considering the adaptive model of comfort. The results showed that it is possible to achieve good thermal performance during summer by passive means only.